Bilateral Giant Fibro Adenoma of Breast (Case Report) - Bresam, ohammad (AL-Kindy College Medical Journal, 2008)
Fibro-adenoma is the most common lesion of the breast, it occurs in25%of asymptomatic women (1,2 )It is usually a disease of early reproductive life, the peak incidence is between the ages15 and 35 years.(3,4) It presents as firm highly mobile, non tender mass .(5)Less than 5% of fibro-adenomas grow rapidly and display the clinical and histologic characteristics of giant fibro-adenoma which is defined as a-tumour either having a diameter greater than 5 cm. And /or amass weighing more than 500 grams, and are conventionally a benign tumor of breast.(6)Giant fibro-adenomas appear as well-circumscribed but not encapsulated masses on mammography and solid and the texture is homogenous and hypoechoic with low level echoes on U/S. (6, 7)It is hormone dependent that lactates during pregnancy and involutes along with the rest of the breast in perimenopause.(5)Excessive estrogen stimulation and /or receptor sensitivity, or lack of estrogen antagonist havebeen implicated in the etiology. (2)Giant fibro-adenoma is often confined to one breast as a solitary mass occupying part or the whole breast and in rare cases it may be multifocal and involve both breasts. (8)Giant fibro-adenomas are benign and do not become malignant. (9)Histological cut surfaces have a lobulated grey-white myxoid semitransparent to dens fibrous appearance, it consist of epithelial and fibrous components, the pericanalicular fibro-adenoma maintains round and oval dilated ductal spaces whereas in the intracanalicular type the ductal lumens are compressed by polypoid fibrous stroma creating slit –like irregular spaces , the ducts are lined by two layers of cells: epithelial and myoepithelial cells and under influence of hormones the ducts become hyper plastic with papillary formation and more than two layers of cells varies from myxoid and hypo cellular to fibrous and moderately cellular . (2)Surgical treatment of giant fibroadenoma ranges from shelling the tumour out in case it occupies part of the breast, to simple mastectomy. (10)